Strength prediction and durability performance of concrete containing coal bottom ash as supplementary cementitious material under aggressive environment - Ali, Sajjad (2019)
Strength prediction and durability of concrete under aggressive environment requires serious attention for all kind of significant concrete structures. However, concrete built with Ordinary Portland Cement (OPC), when exposed to the aggressive environment tends to deteriorate much faster than their projected service life. Therefore, Supplementary Cementitious Material (SCM) need to be introduced to improve the strength and durability performance of concrete. Besides that, prediction of concrete compressive strength is also an important aspect for the safety and quality control of concrete structures. Thus, this study aims to evaluate strength and durability performance of concrete containing Coal Bottom Ash (CBA) as a SCM and to develop empirical equation to predict compressive strength of concrete under normal as well as in aggressive environment. CBA was considered as SCM because it is a huge waste that produced by a coal-based power plants, which creates environmental problems for the global society. Initially, raw CBA was grinded for various periods, to get different particle fineness, then CBA was incorporated as replacement of OPC in concrete at various percentages 10%, 20% and 30% by weight of cement. The optimum percentage replacement and suitable grinding period were determined based on concrete strength performances and it was found that 10% proportion of CBA gives the optimum results at the age of 28 days. Next, the performance of concrete containing 10% CBA was further evaluated in terms of compressive strength, change in weight and degree of damage under aggressive environment such as 5% sodium sulphate (Na2SO4), 5% sodium chloride (NaCl), combination of both (5%Na2SO4+5%NaCl) and seawater at the exposure period of 28, 56, 90 and 180 days. Additionally, microstructural changes in concrete due to aggressive environment were also assessed through Scanning Electron Microscopy (SEM) and X-Ray Diffraction (XRD) techniques. Besides that, the durability performance of concrete containing CBA were also evaluated using Rapid Chloride Permeability Test (RCPT). Moreover, influence of CBA on the drying shrinkage of concrete was also evaluated up to age of 180 days. The experimental results reveal that Control Mix (CM) delivers worst performance when exposed to seawater. However, the incorporation of 10% CBA in concrete enhances its strength performance under seawater exposure. Strength performance of concrete containing 10% CBA exhibits satisfactory in all aggressive environment conditions except 5% NaCl. It was also evaluated that concrete containing 10% CBA exhibits around 45.4% reduction in chloride penetration as compared to CM at 180 days, which indicated its potentiality as durable SCM. Besides that, it was experimentally and theoretically verified that the proposed Bolomey’s Modified Equation (BME) can be used for the prediction of compressive strength of concrete containing ground CBA exposed to normal as well as aggressive environment that particularly represents the marine environment. Hence, this study declared 10% ground CBA as optimum that can be used for future research.